Lithium secondary battery
The lithium secondary battery with a Cu negative electrode having a (200) or (220) orientation and controlled roughness addresses energy density and cycle issues, achieving high energy density and improved cycle characteristics through lithium metal deposition and electrolytic elution.
Patent Information
- Application Number
- JP2022558804
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-02
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-11-02
AI Technical Summary
Conventional lithium secondary batteries suffer from insufficient energy density and cycle characteristics due to issues like dendrite formation and increased weight/volume from mechanical pressure application, which compromises their performance and safety.
A lithium secondary battery design featuring a negative electrode made of Cu with a maximum surface roughness height Rz of 1.0 μm or less and oriented planes of (200) or (220), eliminating the need for negative electrode active materials, allowing lithium metal deposition and electrolytic elution for charging and discharging, thereby enhancing energy density and cycle characteristics.
The battery achieves high energy density of 350 Wh/kg or more with excellent cycle characteristics, improved safety, and reduced weight and volume, minimizing dendrite growth and capacity reduction.
Smart Images

Figure 0007618274000002 
Figure 0007618274000003 
Figure 0007618274000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium secondary battery. [Background technology]
[0002] In recent years, technology for converting natural energy such as solar or wind power into electrical energy has been attracting attention. Accordingly, various secondary batteries have been developed as electricity storage devices that are highly safe and capable of storing a large amount of electrical energy.
[0003] Among them, secondary batteries that charge and discharge by the movement of metal ions between the positive and negative electrodes are known to exhibit high voltage and high energy density, and a typical example is the lithium ion secondary battery. A typical lithium ion secondary battery is one in which an active material capable of retaining lithium is introduced into the positive and negative electrodes, and charging and discharging are performed by the exchange of lithium ions between the positive and negative active materials. In addition, as a secondary battery that does not use an active material in the negative electrode, a lithium metal secondary battery that retains lithium by depositing lithium metal on the surface of the negative electrode has been developed.
[0004] For example, Patent Document 1 discloses a high-energy density, high-power lithium metal anode secondary battery having a volumetric energy density exceeding 1000 Wh / L and / or a mass energy density exceeding 350 Wh / kg when discharged at room temperature at a rate of at least 1 C. Patent Document 1 discloses the use of an ultra-thin lithium metal anode to realize such a lithium metal anode secondary battery.
[0005] Patent Document 2 discloses a lithium secondary battery including a positive electrode, a negative electrode, a separator and an electrolyte interposed therebetween, in which metal particles are formed on a negative electrode current collector, and are transferred from the positive electrode by charging to form lithium metal on the negative electrode current collector in the negative electrode. Patent Document 2 discloses that such a lithium secondary battery can provide a lithium secondary battery with improved performance and life by solving problems caused by the reactivity of lithium metal and problems that occur during the assembly process. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2019-517722 [Patent Document 2] Special Publication No. 2019-537226 Summary of the Invention [Problem to be solved by the invention]
[0007] However, the present inventors have conducted detailed studies on conventional batteries, including those described in the above patent documents, and have found that at least one of the energy density and cycle characteristics is insufficient.
[0008] For example, a typical secondary battery that charges and discharges by transferring metal ions between a positive electrode active material and a negative electrode active material does not have sufficient energy density. In addition, a conventional lithium metal secondary battery that retains lithium by depositing lithium metal on the surface of the negative electrode as described in the above patent document is prone to forming dendrite-like lithium metal on the surface of the negative electrode due to repeated charging and discharging, which makes it prone to short circuits and capacity reduction. As a result, the cycle characteristics are insufficient.
[0009] In addition, in order to suppress the discrete growth of lithium metal precipitation in lithium metal secondary batteries, a method has been developed in which a large physical pressure is applied to the battery to keep the interface between the negative electrode and the separator at a high pressure. However, the application of such high pressure requires a large mechanical mechanism, which increases the weight and volume of the entire battery and reduces the energy density.
[0010] The present invention has been made in consideration of the above problems, and has an object to provide a lithium secondary battery having high energy density and excellent cycle characteristics. [Means for solving the problem]
[0011] A lithium secondary battery according to one embodiment of the present invention includes a positive electrode and a negative electrode having no negative electrode active material. The negative electrode is made of Cu and has a maximum height Rz of surface roughness of 1.0 μm or less and an oriented plane of (200) or (220).
[0012] Such a lithium secondary battery has a high energy density because it is provided with a negative electrode that does not have a negative electrode active material, and lithium metal is deposited on the surface of the negative electrode, and the deposited lithium metal is electrolytically dissolved to perform charging and discharging. In addition, in a lithium secondary battery according to one embodiment of the present invention, the negative electrode is made of Cu with a maximum surface roughness height Rz of 1.0 μm or less and an oriented surface of (200) or (220). This can improve the cycle characteristics of the secondary battery.
[0013] Furthermore, in the lithium secondary battery according to one embodiment of the present invention, the negative electrode Cu is formed by rolling, which allows the negative electrode to be configured using Cu with an orientation plane of (200) or (220), which is suitable for the negative electrode.
[0014] The lithium secondary battery is a lithium secondary battery in which lithium metal is deposited on the surface of the negative electrode and the deposited lithium is dissolved to charge and discharge the battery. According to such an embodiment, the energy density can be further increased.
[0015] In the lithium secondary battery, preferably, no lithium foil is formed on the surface of the negative electrode before the initial charge. According to such an embodiment, there is no need to use highly flammable lithium metal during production, which makes the battery safer and more productive.
[0016] The lithium secondary battery preferably has an energy density of 350 Wh / kg or more. Effect of the Invention
[0017] According to the present invention, it is possible to provide a lithium secondary battery having high energy density and excellent cycle characteristics. [Brief description of the drawings]
[0018] [Figure 1] 1 is a schematic cross-sectional view of a lithium secondary battery according to a first embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view of a lithium secondary battery according to a first embodiment of the present invention; [Diagram 3] FIG. 2 is a schematic cross-sectional view of a lithium secondary battery according to a second embodiment of the present invention. [Figure 4] 1 is a graph showing an example of an X-ray analysis measurement result of Cu used in a negative electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail with reference to the drawings as necessary. In the drawings, the same elements are given the same reference numerals, and duplicated explanations will be omitted. Furthermore, unless otherwise specified, positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings. Furthermore, the dimensional ratios of the drawings are not limited to those shown in the drawings.
[0020] [First embodiment] (lithium secondary battery) Fig. 1 is a schematic cross-sectional view of a lithium secondary battery according to the first embodiment. As shown in Fig. 1, the lithium secondary battery 100 according to the first embodiment includes a positive electrode 120, a negative electrode 130 having no negative electrode active material, and a separator 140 disposed between the positive electrode 120 and the negative electrode 130. The positive electrode 120 has a positive electrode current collector 110 on the surface opposite to the surface facing the separator 140.
[0021] (Negative electrode) The negative electrode 130 does not have a negative electrode active material. In a lithium secondary battery having a negative electrode having a negative electrode active material, it is difficult to increase the energy density due to the presence of the negative electrode active material. On the other hand, the lithium secondary battery 100 of this embodiment has a negative electrode 130 that does not have a negative electrode active material, so such a problem does not occur. That is, the lithium secondary battery 100 of this embodiment has a high energy density because lithium metal is deposited on the surface of the negative electrode 130 and the deposited lithium metal is electrolytically dissolved to perform charging and discharging.
[0022] In this embodiment, "lithium metal is deposited on the surface of the negative electrode" means that lithium metal is deposited on at least one portion of the surface of the negative electrode and the surface of a solid electrolyte interface (SEI) layer, which will be described later, formed on the surface of the negative electrode. Therefore, in the lithium secondary battery 100, lithium metal may be deposited on, for example, the surface of the negative electrode 130 (the interface between the negative electrode 130 and the separator 140).
[0023] In this specification, the term "negative electrode active material" refers to a material for holding lithium ions or lithium metal (hereinafter also referred to as "carrier metal"), which is a charge carrier in a battery, in the negative electrode 130, and may be referred to as a host material for the carrier metal. The mechanism of such holding is not particularly limited, but examples thereof include intercalation, alloying, and occlusion of metal clusters.
[0024] Examples of such negative electrode active materials include, but are not limited to, carbon-based materials, metal oxides, and metals or alloys. Examples of the carbon-based materials include, but are not limited to, graphene, graphite, hard carbon, mesoporous carbon, carbon nanotubes, and carbon nanohorns. Examples of the metal oxides include, but are not limited to, titanium oxide compounds, tin oxide compounds, lithium oxide compounds, and cobalt oxide compounds. Examples of the metals or alloys include, but are not limited to, silicon, germanium, tin, lead, aluminum, gallium, lithium, and alloys containing these metals.
[0025] The negative electrode 130 is made of Cu (copper) that does not have a negative electrode active material. The negative electrode 130 of this embodiment is made of Cu that has been rolled into a foil shape, with the oriented surface being the (200) or (220) surface, and has been subjected to a known surface treatment. The Cu used has a maximum surface roughness Rz of 1.0 μm or less. The maximum surface roughness Rz indicates the difference in height between the highest and lowest positions on the Cu surface. Although the detailed mechanism of action is unknown, it has been confirmed that the cycle characteristics of a secondary battery can be improved by adopting a specific oriented surface (200) or (220) of Cu and controlling the surface roughness Rz, as shown in the examples described later.
[0026] The orientation plane of Cu is defined as the orientation plane corresponding to the location where the highest peak intensity is obtained when the crystal structure of rolled Cu is evaluated by X-ray diffraction measurement (XRD) with the wavelength of characteristic X-rays set to 1.5406 Å. In other words, the orientation plane of Cu is determined based on whether the peak intensity is obtained at a location corresponding to the (111), (200), or (220) plane. For example, when the measurement results shown in Figure 4 are obtained, peaks P1, P2, and P3 correspond to the orientation planes of the (111), (200), and (220), respectively, and the peak with the highest peak intensity is peak P2 corresponding to the (200) plane. Therefore, it can be said that the orientation plane of Cu that gives such measurement results is the (200) plane.
[0027] In this specification, "the negative electrode does not have a negative electrode active material" means that the content of the negative electrode active material in the negative electrode is 10 mass% or less with respect to the entire negative electrode. The content of the negative electrode active material in the negative electrode is preferably 5.0 mass% or less with respect to the entire negative electrode, and may be 1.0 mass% or less, 0.1 mass% or less, or 0.0 mass% or less. Incidentally, the fact that the lithium secondary battery 100 has a negative electrode that does not have a negative electrode active material means that the lithium secondary battery 100 is an anode-free secondary battery, a zero anode secondary battery, or an anodeless secondary battery in the commonly used sense. An anode-free secondary battery refers to a battery system that does not contain any lithium metal or negative electrode active material and is composed only of a current collector on the negative electrode side.
[0028] In addition, in a typical lithium ion secondary battery, the capacity of the negative electrode active material in the negative electrode is set to be the same as the capacity of the positive electrode. Therefore, when the capacity of the negative electrode active material in the negative electrode 130 is smaller than the capacity of the positive electrode 120, for example, 20% or less, 15% or less, 10% or less, or 5% or less, it also means that the "negative electrode does not have a negative electrode active material."
[0029] The average thickness of the negative electrode 130 is preferably 4 μm or more and 20 μm or less, more preferably 5 μm or more and 18 μm or less, and further preferably 6 μm or more and 15 μm or less. According to such an embodiment, the volume occupied by the negative electrode 130 in the lithium secondary battery 100 is reduced, and therefore the energy density of the lithium secondary battery 100 is further improved.
[0030] (positive electrode) Since the positive electrode 120 contains a positive electrode active material, the lithium secondary battery 100 has excellent stability and a high output voltage. In this specification, the "positive electrode active material" means a material for holding lithium ions in the positive electrode 120, and may be referred to as a host material for lithium ions. Examples of such positive electrode active materials include, but are not limited to, metal oxides and metal phosphates. Examples of the metal oxides include, but are not limited to, cobalt oxide-based compounds, manganese oxide-based compounds, and nickel oxide-based compounds. Examples of the metal phosphates include, but are not limited to, iron phosphate-based compounds, and cobalt phosphate-based compounds. Typical positive electrode active materials include LiCoO2, LiNi x Co y Mn z O(x+y+z=1), LiNi x Mn y O(x+y=1), LiNiO2, LiMn2O4, LiFePO, LiCoPO, LiFeOF, LiNiOF, and TiS2. The above-mentioned positive electrode active materials may be used alone or in combination of two or more.
[0031] The positive electrode 120 may contain components other than the above-mentioned positive electrode active material. Such components are not particularly limited, but may include, for example, known conductive assistants, binders, solid polymer electrolytes, and inorganic solid electrolytes.
[0032] The conductive assistant in the positive electrode 120 is not particularly limited, but examples thereof include carbon black, single-wall carbon nanotubes (SWCNT), multi-wall carbon nanotubes (MWCNT), carbon nanofibers (CF), acetylene black, etc. The binder is not particularly limited, but examples thereof include polyvinylidene fluoride, polytetrafluoroethylene, styrene butadiene rubber, acrylic resin, polyimide resin, etc.
[0033] The content of the positive electrode active material in the positive electrode 120 may be, for example, 50% by mass or more and 100% by mass or less with respect to the entire positive electrode 120. The content of the conductive assistant may be, for example, 0.5% by mass or more and 30% by mass or less with respect to the entire positive electrode 120. The content of the binder may be, for example, 0.5% by mass or more and 30% by mass or less with respect to the entire positive electrode 120. The total content of the solid polymer electrolyte and the inorganic solid electrolyte may be, for example, 0.5% by mass or more and 30% by mass or less with respect to the entire positive electrode 120.
[0034] (Positive electrode current collector) A positive electrode current collector 110 is formed on one side of the positive electrode 120. There are no particular limitations on the positive electrode current collector 110 as long as it is a conductor that does not react with lithium ions in the battery. An example of such a positive electrode current collector is aluminum.
[0035] The average thickness of the positive electrode current collector 110 is preferably 4 μm or more and 20 μm or less, more preferably 5 μm or more and 18 μm or less, and further preferably 6 μm or more and 15 μm or less. According to such an embodiment, the volume occupied by the positive electrode current collector 110 in the lithium secondary battery 100 is reduced, and therefore the energy density of the lithium secondary battery 100 is further improved.
[0036] (Separator) The separator 140 is a member for preventing the battery from short-circuiting by isolating the positive electrode 120 and the negative electrode 130, while ensuring ionic conductivity of lithium ions that serve as charge carriers between the positive electrode 120 and the negative electrode 130, and is made of a material that does not have electronic conductivity and does not react with lithium ions. The separator 140 also plays a role in retaining the electrolyte. The separator 140 is not limited as long as it plays the above role, and is made of, for example, porous polyethylene (PE), polypropylene (PP), or a laminated structure thereof.
[0037] The separator 140 may be coated with a separator coating layer. The separator coating layer may cover both sides of the separator 140, or may cover only one side. The separator coating layer is not particularly limited as long as it is a material that has ion conductivity and does not react with lithium ions, but it is preferable that the separator coating layer is capable of firmly bonding the separator 140 and a layer adjacent to the separator 140. Examples of such a separator coating layer include, but are not particularly limited to, polyvinylidene fluoride (PVDF), a mixture of styrene butadiene rubber and carboxymethyl cellulose (SBR-CMC), polyacrylic acid (PAA), lithium polyacrylate (Li-PAA), polyimide (PI), polyamideimide (PAI), and a binder such as aramid. The separator coating layer may include inorganic particles such as silica, alumina, titania, zirconia, magnesium oxide, magnesium hydroxide, and lithium nitrate added to the binder.
[0038] The average thickness of the separator 140 is preferably 20 μm or less, more preferably 18 μm or less, and even more preferably 15 μm or less. According to such an embodiment, the volume occupied by the separator 140 in the lithium secondary battery 100 is reduced, and the energy density of the lithium secondary battery 100 is further improved. Moreover, the average thickness of the separator 140 is preferably 5 μm or more, more preferably 7 μm or more, and even more preferably 10 μm or more. According to such an embodiment, the positive electrode 120 and the negative electrode 130 can be more reliably isolated from each other, and the battery can be further prevented from being short-circuited.
[0039] (electrolyte) The lithium secondary battery 100 may have an electrolytic solution. The electrolytic solution may be impregnated into the separator 140, or the lithium secondary battery 100 may be filled with the electrolytic solution to form a finished product. The electrolytic solution is a solution containing an electrolyte and a solvent and having ion conductivity, and acts as a conductive path for lithium ions. Therefore, the lithium secondary battery 100 having the electrolytic solution has a further reduced internal resistance and further improved energy density, capacity, and cycle characteristics.
[0040] The electrolyte is not particularly limited as long as it is a salt, and examples thereof include salts of Li, Na, K, Ca, and Mg. A lithium salt is preferably used as the electrolyte. The lithium salt is not particularly limited, and examples thereof include LiI, LiCl, LiBr, LiF, LiBF4, LiPF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2CF3CF3)2, LiB(O2C2H4)2, LiB(O2C2H4)F2, LiB(OCOCF3)4, LiNO3, and Li2SO4. From the viewpoint of further improving the energy density, capacity, and cycle characteristics of the lithium secondary battery 100, the lithium salt is preferably LiN(SO2F)2. The above lithium salts are used alone or in combination of two or more.
[0041] The solvent is not particularly limited, but examples thereof include dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, acetonitrile, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, chloroethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, trifluoromethyl propylene carbonate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, nonafluorobutyl methyl ether, nonafluorobutyl ethyl ether, tetrafluoroethyl tetrafluoropropyl ether, trimethyl phosphate, and triethyl phosphate. The above-mentioned solvents may be used alone or in combination of two or more.
[0042] (Use of lithium secondary batteries) 2 shows one mode of use of the lithium secondary battery of this embodiment. In the lithium secondary battery 100, a positive electrode terminal 220 and a negative electrode terminal 230 for connecting the lithium secondary battery 100 to an external circuit are joined to a positive electrode current collector 110 and a negative electrode 130, respectively. The lithium secondary battery 100 is charged and discharged by connecting the negative electrode terminal 230 to one end of the external circuit and the positive electrode terminal 220 to the other end of the external circuit.
[0043] The lithium secondary battery 100 is charged by applying a voltage between the positive electrode terminal 220 and the negative electrode terminal 230 such that a current flows from the negative electrode terminal 230 through an external circuit to the positive electrode terminal 220. Charging the lithium secondary battery 100 causes deposition of lithium metal at the interface between the negative electrode 130 and the separator 140.
[0044] In the lithium secondary battery 100, a solid electrolyte interface layer (SEI layer) 210 may be formed at the interface between the negative electrode 130 and the separator 140 by initial charging. The SEI layer 210 to be formed is not particularly limited, and may contain, for example, an inorganic compound containing lithium and an organic compound containing lithium. The typical average thickness of the SEI layer is 1 nm or more and 10 μm or less.
[0045] When the SEI layer 210 is formed in the lithium secondary battery 100, the lithium metal that precipitates during charging of the lithium secondary battery 100 may precipitate at the interface between the negative electrode 130 and the SEI layer 210, or may precipitate at the interface between the SEI layer 210 and the separator 140.
[0046] When the positive electrode terminal 220 and the negative electrode terminal 230 are connected to the charged lithium secondary battery 100, the lithium secondary battery 100 is discharged. The lithium metal precipitated at the interface between the negative electrode 130 and the SEI layer 210 and / or the interface between the SEI layer 210 and the separator 140 is electrolytically dissolved.
[0047] (Lithium secondary battery manufacturing method) The method for manufacturing the lithium secondary battery 100 as shown in FIG. 1 is not particularly limited as long as it is a method capable of manufacturing a lithium secondary battery having the above-mentioned configuration, and examples thereof include the following methods.
[0048] First, the positive electrode 120 is prepared by a known manufacturing method or by purchasing a commercially available product. The positive electrode 120 is manufactured, for example, as follows. The above-mentioned positive electrode active material, a known conductive assistant, and a known binder are mixed to obtain a positive electrode mixture. The compounding ratio may be, for example, 50% by mass or more and 99% by mass or less of the positive electrode active material, 0.5% by mass or less and 30% by mass or less of the conductive assistant, and 0.5% by mass or less and 30% by mass or less of the binder, relative to the entire positive electrode mixture. The obtained positive electrode mixture is applied to one side of a metal foil (e.g., Al foil) having a predetermined thickness (e.g., 5 μm or more and 1 mm or less) as a positive electrode current collector, and press-molded. The obtained molded body is punched out to a predetermined size by punching to obtain the positive electrode 120.
[0049] Next, the above-mentioned negative electrode material, for example, a Cu foil having a thickness of 1 μm or more and 1 mm or less that has been subjected to an anti-rust treatment, is used as the negative electrode 130 .
[0050] Next, the separator 140 having the above-mentioned structure is prepared. The separator 140 may be produced by a conventionally known method, or a commercially available product may be used.
[0051] The positive electrode 120, the separator 140, and the negative electrode 130 obtained as described above are laminated in this order to obtain a laminate. The obtained laminate is enclosed in a sealed container together with an electrolyte solution to obtain a lithium secondary battery 100. The sealed container is not particularly limited, but examples thereof include a laminate film.
[0052] [Second embodiment] (lithium secondary battery)
[0053] 3 is a schematic cross-sectional view of a lithium secondary battery according to the second embodiment. As shown in FIG. 3, the lithium secondary battery 300 according to the second embodiment includes a positive electrode collector 110, a positive electrode 120 having a positive electrode active material formed on one side of the positive electrode collector 110, a negative electrode 130 having no negative electrode active material, and a solid electrolyte 310 disposed between the positive electrode 120 and the negative electrode 130. The configurations and preferred aspects of the positive electrode collector 110, the positive electrode 120, and the negative electrode 130 are the same as those of the lithium secondary battery 100 according to the first embodiment, except for the points described below, and the lithium secondary battery 300 exhibits the same effects as the lithium secondary battery 100.
[0054] (solid electrolyte) Generally, in batteries with a liquid electrolyte, the physical pressure applied from the electrolyte to the negative electrode surface tends to vary depending on the location due to fluctuations in the liquid. On the other hand, since the lithium secondary battery 300 includes the solid electrolyte 310, the pressure applied from the solid electrolyte 310 to the negative electrode 130 surface becomes more uniform, and the shape of the carrier metal precipitated on the surface of the negative electrode 130 can be made more uniform. That is, according to this embodiment, the carrier metal precipitated on the surface of the negative electrode 130 is further prevented from growing in a dendritic shape, and the cycle characteristics of the lithium secondary battery 300 become more excellent.
[0055] The solid electrolyte 310 is not particularly limited as long as it is generally used in lithium solid secondary batteries, but a known material can be appropriately selected depending on the application of the lithium secondary battery 300 and the type of carrier metal. The solid electrolyte 310 preferably has ionic conductivity and no electronic conductivity. By having the solid electrolyte 310 have ionic conductivity and no electronic conductivity, the internal resistance of the lithium secondary battery 300 is further reduced and short circuits inside the lithium secondary battery 300 can be further suppressed. As a result, the energy density, capacity, and cycle characteristics of the lithium secondary battery 300 are further improved.
[0056] The solid electrolyte 310 is not particularly limited, but examples thereof include those containing a resin and a lithium salt. Examples of such resins are not particularly limited, but examples thereof include resins having an ethylene oxide unit in the main chain and / or side chain, acrylic resins, vinyl resins, ester resins, nylon resins, polysiloxanes, polyphosphazenes, polyvinylidene fluorides, polymethyl methacrylate, polyamides, polyimides, aramids, polylactic acids, polyethylenes, polystyrenes, polyurethanes, polypropylenes, polybutylenes, polyacetals, polysulfones, and polytetrafluoroethylenes. The above-mentioned resins are used alone or in combination of two or more.
[0057] The lithium salt contained in the solid electrolyte 310 is not particularly limited, but examples thereof include LiI, LiCl, LiBr, LiF, LiBF4, LiPF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2CF3CF3)2, LiB(O2C2H4)2, LiB(O2C2H4)F2, LiB(OCOCF3)4, LiNO3, and Li2SO4. The above-mentioned lithium salts may be used alone or in combination of two or more.
[0058] In general, the content ratio of the resin to the lithium salt in the solid electrolyte is determined by the ratio ([Li] / [O]) of the oxygen atoms in the resin to the lithium atoms in the lithium salt. In the solid electrolyte 310, the content ratio of the resin to the lithium salt is adjusted so that the ratio ([Li] / [O]) is preferably 0.02 or more and 0.20 or less, more preferably 0.03 or more and 0.15 or less, and even more preferably 0.04 or more and 0.12 or less.
[0059] The solid electrolyte 310 may contain components other than the resin and lithium salt. Such components are not particularly limited, but include, for example, a solvent and a salt other than the lithium salt. The salt other than the lithium salt is not particularly limited, but includes, for example, salts of Li, Na, K, Ca, and Mg.
[0060] The solvent is not particularly limited, but examples thereof include those exemplified as the electrolyte that the lithium secondary battery 100 may contain.
[0061] The average thickness of the solid electrolyte 310 is preferably 20 μm or less, more preferably 18 μm or less, and further preferably 15 μm or less. According to such an embodiment, the volume occupied by the solid electrolyte 310 in the lithium secondary battery 300 is reduced, and the energy density of the lithium secondary battery 300 is further improved. Also, the average thickness of the solid electrolyte 310 is preferably 5 μm or more, more preferably 7 μm or more, and further preferably 10 μm or more. According to such an embodiment, the positive electrode 120 and the negative electrode 130 can be more reliably isolated from each other, and the battery can be further prevented from being short-circuited.
[0062] In this specification, the term "solid electrolyte" includes gel electrolytes. The gel electrolyte is not particularly limited, but may include, for example, a polymer, an organic solvent, and a lithium salt. The polymer in the gel electrolyte is not particularly limited, but may include, for example, a copolymer of polyethylene and / or polyethylene oxide, polyvinylidene fluoride, and a copolymer of polyvinylidene fluoride and hexafluoropropylene.
[0063] In addition, in FIG. 3, a solid electrolyte interface layer (SEI layer) may be formed on the surface of the negative electrode 130. The SEI layer to be formed is not particularly limited, and may contain, for example, an inorganic compound containing lithium and an organic compound containing lithium. The typical average thickness of the SEI layer is 1 nm or more and 10 μm or less. When the SEI layer is formed in the lithium secondary battery 300, lithium metal precipitated by charging may precipitate at the interface between the negative electrode 130 and the SEI layer, or may precipitate at the interface between the SEI layer and the solid electrolyte 310.
[0064] (Secondary battery manufacturing method) The lithium secondary battery 300 can be manufactured in the same manner as the manufacturing method of the lithium secondary battery 100 according to the first embodiment described above, except that a solid electrolyte is used instead of the separator.
[0065] The method for producing the solid electrolyte 310 is not particularly limited as long as it can obtain the above-mentioned solid electrolyte 310, but may be, for example, as follows. A resin conventionally used in solid electrolytes and a lithium salt (for example, the resin and lithium salt described above as the resin that the solid electrolyte 310 may contain) are dissolved in an organic solvent. The obtained solution is cast onto a molding substrate to a predetermined thickness to obtain the solid electrolyte 310. Here, the compounding ratio of the resin and the lithium salt may be determined by the ratio ([Li] / [O]) of the oxygen atoms of the resin to the lithium atoms of the lithium salt, as described above. The ratio ([Li] / [O]) is, for example, 0.02 or more and 0.20 or less. The organic solvent is not particularly limited, but acetonitrile may be used, for example. The molding substrate is not particularly limited, but PET film or glass substrate may be used, for example.
[0066] The above-described embodiment is an example for explaining the present invention, and is not intended to limit the present invention to only this embodiment. The present invention can be modified in various ways without departing from the gist of the invention.
[0067] For example, in the lithium secondary battery 100 of the first embodiment and the lithium secondary battery 300 of the second embodiment, the positive electrode 120 may be formed on both sides of the positive electrode current collector 110. In this case, the lithium secondary battery includes two positive electrodes 120, two negative electrodes 130 arranged to face each positive electrode 120, and two separators 140 or solid electrolytes 310 arranged between the positive electrodes 120 and the negative electrodes 130. According to such an embodiment, the capacity of the lithium secondary battery can be further improved.
[0068] The lithium secondary battery of the present embodiment may be a lithium solid secondary battery, which does not require the use of an electrolyte, and therefore does not cause the problem of electrolyte leakage, thereby further improving the safety of the battery.
[0069] The lithium secondary battery of this embodiment may have a current collector arranged so as to contact the negative electrode. Such a current collector is not particularly limited, but may be, for example, a current collector that can be used as a negative electrode material. If the lithium secondary battery does not have a negative electrode current collector, the negative electrode itself acts as a current collector.
[0070] In the lithium secondary battery of this embodiment, terminals for connecting to an external circuit may be attached to the positive electrode collector and the negative electrode. For example, a metal terminal (e.g., Al, Ni, etc.) having a thickness of 10 μm to 1 mm may be bonded to one or both of the positive electrode collector and the negative electrode. A conventionally known method may be used as a bonding method, and ultrasonic welding may be used, for example.
[0071] In this specification, "high energy density" or "having a high energy density" means that the capacity per unit total volume or total mass of the battery is high, and is preferably 800 Wh / L or more or 350 Wh / kg or more, more preferably 900 Wh / L or more or 400 Wh / kg or more, and even more preferably 1000 Wh / L or more or 450 Wh / kg or more.
[0072] In addition, in this specification, "having excellent cycle characteristics" means that the capacity of the battery is reduced at a low rate before and after a number of charge / discharge cycles that can be expected in normal use. That is, when comparing the first discharge capacity after the initial charge / discharge and the capacity after a number of charge / discharge cycles that can be expected in normal use, the capacity after the charge / discharge cycle is almost not reduced compared to the first discharge capacity after the initial charge / discharge. Here, the "number of times that can be expected in normal use" is, for example, 30 times, 50 times, 70 times, 100 times, 300 times, or 500 times, depending on the application of the lithium secondary battery. In addition, "the capacity after the charge / discharge cycle is almost not reduced compared to the first discharge capacity after the initial charge / discharge" means, for example, that the capacity after the charge / discharge cycle is 75% or more, 80% or more, or 85% or more compared to the first discharge capacity after the initial charge / discharge, depending on the application of the lithium secondary battery. EXAMPLES
[0073] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.
[0074] [Making a lithium secondary battery] The steps for manufacturing the lithium secondary battery were carried out as follows.
[0075] (Preparation of the negative electrode) A 10 μm thick Cu foil prepared for each of the following examples is used as the negative electrode. The negative electrode is subjected to anti-rust treatment.
[0076] (Preparation of separator) A separator of a given size (50 mm×50 mm) was prepared, in which both sides of a 12 μm polyethylene microporous membrane were coated with 2 μm polyvinylidene fluoride (PVDF).
[0077] (Preparation of positive electrode) LiNi as the positive electrode active material 0.85 Co 0.12 Mn 0.03 A mixture of 96 parts by mass of O2, 2 parts by mass of carbon black as a conductive assistant, and 2 parts by mass of polyvinylidene fluoride (PVDF) as a binder was applied to one side of a 12 μm Al foil as a positive electrode current collector and press molded. The obtained molded body was punched out to a predetermined size (40 mm × 40 mm) by punching to obtain a positive electrode.
[0078] (Battery Assembly) As an electrolyte, a dimethoxyethane (DME) solution of 4M LiN(SO2F)2 (LFSI) was prepared. Next, a laminate was obtained by stacking the positive electrode, the separator, and the negative electrode in this order. When a buffer functional layer was formed on the separator, the buffer functional layer was made to face the negative electrode, and when a metal layer was formed on the negative electrode, the stacking was performed so that the metal layer was made to face the separator. Furthermore, a 100 μm Al terminal and a 100 μm Ni terminal were joined to the positive electrode and the negative electrode, respectively, by ultrasonic welding, and then inserted into the laminate exterior body. Next, the above electrolyte was injected into the exterior body. The exterior body was sealed to obtain a lithium secondary battery.
[0079] [Example 1] A secondary battery was produced by using a rolled Cu electrode with a (200) oriented surface and a maximum surface roughness Rz of 0.3 μm as the negative electrode, and including a positive electrode, a separator, and a negative electrode.
[0080] [Example 2] A secondary battery was produced by using a negative electrode made of Cu with a (200) oriented surface and a maximum height Rz of surface roughness of 0.7 μm formed by rolling, and including a positive electrode, a separator, and a negative electrode.
[0081] [Example 3] A secondary battery was fabricated using a negative electrode made of Cu with a (220) oriented surface and a maximum surface roughness Rz of 0.7 μm, which was formed by rolling, and equipped with a positive electrode, a separator, and a negative electrode.
[0082] [Example 4] A secondary battery was produced by using a negative electrode made of Cu with a (200) oriented surface and a maximum height Rz of surface roughness of 1.0 μm formed by rolling, and including a positive electrode, a separator, and a negative electrode.
[0083] [Comparative Example 1] A secondary battery was produced by using a rolled Cu negative electrode having a (200) oriented surface and a maximum height Rz of surface roughness of 1.2 μm as a positive electrode, a separator, and a negative electrode.
[0084] [Comparative Example 2] A secondary battery was produced using an electrolytic copper foil formed by electroplating, with an orientation surface of (111) and a maximum height of surface roughness Rz of 0.8 μm as the negative electrode, and including a positive electrode, a separator, and a negative electrode.
[0085] [Comparative Example 3] A secondary battery was produced using an electrolytic copper foil formed by electroplating, with an orientation surface of (111) and a maximum height of surface roughness Rz of 1.5 μm as the negative electrode, and including a positive electrode, a separator, and a negative electrode.
[0086] [Evaluation of energy density and cycle characteristics] The cycle characteristics of the lithium secondary batteries produced in each of the Examples and Comparative Examples were evaluated as follows.
[0087] The lithium secondary battery was fabricated at 0.2 mAh / cm 2 After charging until the voltage reached 4.2V (initial charge), the battery discharged 0.2mAh / cm 2 The battery was discharged at 1.0 mAh / cm until the voltage reached 3.0 V (initial discharge). 2 After charging until the voltage reached 4.2V, the battery was charged at 1.0mAh / cm 2 The charge-discharge cycle was repeated for another 49 cycles at 25°C, with the battery being discharged at 100°C until the voltage reached 3.0V. In all of the Examples and Comparative Examples, the capacity (initial capacity) determined from the initial charge was 60mAh. The ratio of the discharge capacity determined from the discharge at the 50th charge-discharge cycle to the discharge capacity determined from the discharge at the 2nd charge-discharge cycle, counting the initial charge-discharge cycle as the 1st cycle, was calculated as the capacity retention rate (%) and used as an index of cycle characteristics. A higher capacity retention rate means better cycle characteristics. The capacity retention rates in each example are shown in Table 1.
[0088] [Table 1]
[0089] As shown in Table 1, the lithium secondary batteries of Examples 1 to 4 exhibited a relatively high capacity retention rate of 88% to 90%. On the other hand, the lithium secondary batteries of Comparative Examples 1 to 3 exhibited a capacity retention rate of 70 to 71%. That is, it is found that Examples 1 to 4, which used Cu with an oriented plane of (200) or (220) and a maximum height Rz of surface roughness of 1.0 μm or less, had a higher capacity retention rate and better cycle characteristics than Comparative Examples 1 to 3. [Industrial Applicability]
[0090] INDUSTRIAL APPLICABILITY The lithium secondary battery of the present invention has high energy density and excellent cycle characteristics, and therefore has industrial applicability as an electricity storage device for various applications. [Explanation of symbols]
[0091] 100, 300... lithium secondary battery, 110... positive electrode current collector, 120... positive electrode, 130... negative electrode, 140... separator, 210... solid electrolyte interface layer (SEI layer), 220... positive electrode terminal, 230... negative electrode terminal, 310... solid electrolyte.
Claims
1. A lithium secondary battery comprising a positive electrode and a negative electrode having no negative electrode active material, The negative electrode has a maximum height Rz of surface roughness of 1.0 μm or less, and is made of Cu with an oriented surface of a (200) or (220) plane, and the oriented surface corresponds to a portion where the highest peak intensity is obtained among peak intensities obtained when evaluated by X-ray diffraction measurement. Lithium secondary battery.
2. The Cu is formed by rolling.
2. The lithium secondary battery according to claim 1.
3. Lithium metal is deposited on the surface of the negative electrode, and the deposited lithium metal is dissolved to perform charging and discharging.
3. The lithium secondary battery according to claim 1 or 2.
4. Prior to initial charging, no lithium foil is formed on the surface of the negative electrode; 4. The lithium secondary battery according to claim 1.
5. The energy density is 350 Wh / kg or more. The lithium secondary battery according to any one of claims 1 to 4.
Citation Information
Patent Citations
Copper foil excellent in adhesive property to coating layer
JP1999310864A
Lithium secondary battery
JP2001243957A
Collector, negative electrode, and secondary battery
JP2009004370A
Negative electrode current collector, negative electrode, and lithium secondary battery
JP2019140057A
Secondary battery and manufacturing method thereof
JP2019501480A